"Atypical" atypical parkinsonism: Critical appraisal of a cohort. (April 2017) - Hirschbichler, Stephanie T.; Erro, Roberto; Ganos, Christos; Stamelou, Maria; Batla, Amit; Balint, Bettina; Bhatia, Kailash P.
Abstract: Background: Atypical parkinsonian conditions such as multiple system atrophy (MSA), progressive supranuclear palsy (PSP), corticobasal syndrome (CBS) and Dementia with Lewy bodies (DLB) comprise 10–15% of parkinsonian syndromes. Misdiagnosis with Parkinson disease (PD) and within the entities is common, given the absence of reliable biomarkers. However a correct diagnosis is not only important in clinical practice, but also crucial for any trial attempting to identify biomarkers or new treatments. Methods: Consecutive patients, who were referred to our tertiary center with a diagnosis of a particular AP were included and the medical records were reviewed retrospectively. We applied each set of current diagnostic research criteria to the respective cohort to see which features fit in and if there are any additional atypical features "outside" the classic definition. Results: Sixty-nine patients were recruited between January 2013 and May 2015 clinically presenting with one of the following phenotypes: 14 MSA, 24 PSP, 19 CBS and 12 DLB. Up to 49% showed additional "atypical" features and approximately 10% eventually received an alternative diagnosis, in half of whom this being based on genetic testing. Conclusions: In a subset of our patients, despite the final diagnosis of an AP being maintained, there were additional "atypical" features. It remains to be seen if these reflect the clinical heterogeneity of APs, or should prompt a search for an alternative diagnosis. The search for biomarkers is more likely to be successful in homogenous groups of "typical" patients, hence the importance of recognizing "atypical" features. Highlights: Retrospective review of medical records of 69 patients referred to a movement disorder clinic in a tertiary referral center. A considerable proportion of patients fitting one of the AP criteria have "atypical" features (49%). Genetic conditions can mimic the clinical phenotype of AP – and are referred to as "AP- phenocopies" or "AP-look a likes". Identifying homogeneous patient groups is crucial for future research on pathophysiology and neuro-protective interventions.